Troubleshooting Difficult Bile Duct Access: Advanced ERCP Cannulation Techniques, Percutaneous Biliary Drainage, or EUS-Guided Rendezvous Technique? - Ting-Ting Chan; Marcus C. H. Chew; Raymond S. Y. Tang (Gastroenterology Insights, 2021)
Despite experienced hands and availability of various well-designed catheters and wires, selective bile duct cannulation may still fail in 10–20% of cases during endoscopic retrograde cholangiopancreatography (ERCP). In case standard ERCP cannulation technique fails, salvage options include advanced ERCP cannulation techniques such as double-guidewire technique (DGW) with or without pancreatic stenting and precut papillotomy, percutaneous biliary drainage (PBD), and endoscopic ultrasound-guided Rendezvous (EUS-RV) ERCP. If the pancreatic duct is inadvertently entered during cannulation attempts, DGW technique is a reasonable next step, which can be followed by pancreatic stenting to reduce risks of post-ERCP pancreatitis (PEP). Studies suggest that early precut papillotomy is not associated with a higher risk of PEP, while needle-knife fistulotomy is the preferred method. For patients with critical clinical condition who may not be fit for endoscopy, surgically altered anatomy in which endoscopic biliary drainage is not feasible, and non-communicating multisegmental biliary obstruction, PBD has a unique role to provide successful biliary drainage efficiently in this particular population. As endoscopic ultrasound (EUS)-guided biliary drainage techniques advance, EUS-RV ERCP has been increasingly employed to guide bile duct access and cannulation with satisfactory clinical outcomes and is especially valuable for benign pathology at centres where expertise is available. Endoscopists should become familiar with each technique’s advantages and limitations before deciding the most appropriate treatment that is tailored to patient’s anatomy and clinical needs.